Blended Learning: Engaging 21st Century Learners in Innovative Teaching and Learning Technology - Dr Priyanka Singh Niranjan (International Journal of Advanced Science and Technology, 2020)
The 21st Century Learning Landscape is a very different place from where it used to be. We are experiencing a drastic change in our education system. Technology is driving this change and now a day a Leading trend in education is Blended learning. It conglomerates traditional classroom learning with computer-assisted learning and it also often helps the learners to achieve better learning result has been shown in this field. The core objective of the paper is to study the characteristics of 21st Century Learners and also to study what is Blended learning and to see how the blended educational strategy effects the achievement of eight class students in social science subject (Experimental Study). A Sample was taken from Delhi/NCR region. It consists of 100 male and female students in experimental group and control group. Achievement test was used to achieve the objective. It is found that there is significant increase in the achievement of the experiment group than the control group. Therefore, we can conclude that blended teaching strategy has significant difference on achievement of students.